On-Chip Electro-Static Discharge (ESD) Protection for Radio-Frequency Integrated Circuits - Cui, Q (Springer, 2016)
This book enables readers to design effective ESD protection solutions for all mainstream RF fabrication processes (GaAs pHEMT, SiGe HBT, CMOS). The new techniques introduced by the authors have much higher protection levels and much lower parasitic effects than those of existing ESD protection devices. The authors describe in detail the ESD phenomenon, as well as ESD protection fundamentals, standards, test equipment, and basic design strategies. Readers will benefit from realistic case studies of ESD protection for RFICs and will learn to increase significantly modern RFICs’ ESD safety level, while maximizing RF performance.